2014
DOI: 10.1016/j.bmcl.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput docking for the identification of new influenza A virus polymerase inhibitors targeting the PA–PB1 protein–protein interaction

Abstract: A high-throughput molecular docking approach was successfully applied for the selection of potential inhibitors of the Influenza RNA-polymerase which act by targeting the PA-PB1 protein-protein interaction. Commercially available compounds were purchased and biologically evaluated in vitro using an ELISA-based assay. As a result, some compounds possessing a 3-cyano-4,6-diphenyl-pyridine nucleus emerged as effective inhibitors with the best ones showing IC50 values in the micromolar range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…While our transmissible H7N1 virus does not harbor mutations that confer resistance to existing antivirals, amantadine resistance is prevalent in circulating human influenza viruses and oseltamivir-resistant viruses are being isolated with increasing frequency (50)(51)(52). The mutations in NP and PB2 highlight the need for strategies that specifically target the viral polymerase, and several compounds are currently under development (53)(54)(55)(56)(57)(58). For example, nucleozin causes NP oligomerization in the cytoplasm, limiting nuclear import and assembly of vRNPs (55), and cycloheptathiophene-3-carboxamide derivatives inhibit PB1-PA interactions (56).…”
Section: Discussionmentioning
confidence: 99%
“…While our transmissible H7N1 virus does not harbor mutations that confer resistance to existing antivirals, amantadine resistance is prevalent in circulating human influenza viruses and oseltamivir-resistant viruses are being isolated with increasing frequency (50)(51)(52). The mutations in NP and PB2 highlight the need for strategies that specifically target the viral polymerase, and several compounds are currently under development (53)(54)(55)(56)(57)(58). For example, nucleozin causes NP oligomerization in the cytoplasm, limiting nuclear import and assembly of vRNPs (55), and cycloheptathiophene-3-carboxamide derivatives inhibit PB1-PA interactions (56).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, quite potent inhibitors of PB2 cap-binding were recently developed with few reported interactions with cellular partners [70,71]. The endonuclease domain represents a specific target with an excellent druggable site [73][74][75][76][77][78]83,84]. Moreover, the PA--PB1 interaction represents an attractive target for inhibitors since the association of PA and PB1 subunits is essential for replication [85][86][87][88], and the sequence of these domains is highly conserved [89,90].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, interfering with the assembly of the RdRp complex could be a way to fight against influenza infection. A large library of drugs, in particular benzofurazan derivatives, was found to act by inhibiting the viral RdRp complex through disruption of the complex formed by PA and PB1 subunits [81][82][83][84]. Since the association of these subunits is essential for replication [85][86][87][88] and the sequence of this domain is highly conserved [89,90] this interaction represents an attractive target for inhibitors.…”
Section: Pb2 Cap-bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another target is the highly conserved PB1 binding site on PA, given that the interaction is crucial to polymerase assembly and activity [21,22,[33][34][35]151]. Moreover, two-dimensional structure analysis has revealed that the core of the PB1 interaction interface consists of only five residues (P5, L7, L8, F9 and L10) in a 310-helix [21,33], suggesting that the development of antiviral peptide or peptidomimetic is feasible [152]. The third target is the host interaction partners of PA that are hijacked for virus transcription or replication, including hCLe [118][119][120], svRNA [121,122] and MCM [123].…”
Section: Immunoregulatory Functions Of Pa Proteinmentioning
confidence: 99%